Response of Nursing Staff to Burnout in Burn Centers of Tehran - F Rafii (نشریه پرستاری ایران, 2007)
Background & Aim:Nursing care in a burn center is demanding intensive care which provokes emotional responses among staff. Every nurse who cares for a patient with burn injury, knows that stress is a part of working in this field and organizational problems and issues related to the patients in these centers leads to intense reactions in the staff which finally results in burnout and exerts negative influences on nursing care. Therefore, the objective of this paper as part of an extensive research was identifying the nature of burn nurses' responses to burnout. Material & Method: Grounded theory was used in this study. Thirty- eight participants were recruited by purposeful and theoretical sampling and data were generated by unstructured interviews and participant observations. Constant comparison was used for data generation in this study. Results: Participants represented negative dimensions in response to stress and burnout. These responses emerged as emotional, attitudinal, psychosomatic behavioral, and organizational dimensions. Emotional dimension included personal and professional desperation attitudinal dimension included depersonalization and negativity psychosomatic, responses included physical and psychological attrition behavioral response included intolerance and justification and organizational dimension included irresponsiveness care and declining performance. Conclusion: Burnout impressed all dimensions of participants' entities and in this way, influenced quality of nursing care negatively. The process of actions and interactions of the nursing staff emerged as a response to situations and context of burn centers during time period. These responses sometimes were represented spontaneously, and sometimes as means for reducing the influence of environmental stressors. Some of these responses focused on the kind of care, and some involved feelings and emotions of the participants. But the participants' bodies were also the target of some responses.  Modifying macro and micro conditions governing burn centers is necessary. Nurse administrators concerning about signs and symptoms of burnout, and also executing stress management programs will reduce stress and distress in the nurses and also improve the quality of nursing care.